State elites and the new poverty agenda in Bangladesh - Neil Webster; Zarina Rahman Khan; Abu Hossain Muhammad Ahsan; Akhter Hussain; Mahbubur Rahman (Danish Institute for International Studies (DIIS), 2009)
The Poverty Reduction Strategy Paper is a relatively new term in Bangladesh development assistance yet it possesses the characteristic of much else in the aid industry, namely being donor driven, locally produced, and of indeterminate ownership. In line with a number of other developing countries Bangladesh prepared first an Interim-PRSP and thereafter a full PRSP in 2005. Subsequently a second PRSP was drafted. The paper argues that introduction of the PRSP in Bangladesh replaced the earlier Five Year Plans but it did not change the approach towards dealing with development. Rather, the PRSP process transformed the way planning is done, budgets are coordinated, and policy implementation monitored. The impact has been more about the process of policymaking than its substance. The new government that came to power in the recent elections held in January 2009 had declared in April 2009 that it intended to return to a 5 year planning process in 2011. More recently it also decided to realign the PRSP document with its election manifesto. Thus it appears that a PRSP and a 5 year plan will co-exist in the coming years, but this is taking place in a context of the declining importance of aid in the Bangladesh economy.
Keywords: 330; Entwicklungspolitik; Armutspolitik; Bangladesch